Identifying Linked and Convergent Argument Structures: A Problem Unsolved - Yu, Shiyang; Zenker, Frank (Informal Logic)

(untitled) (Informal Logic, 2022)
To analyze the argument structure, the linked vs convergent distinction is crucial. In applying this distinction, argumentation scholars test for variations of argument strength under premise revision. A relevance-based test assesses whether an argument’s premises are individually relevant to its conclusion, while a support-based test assesses whether premises support the conclusion independently. Both criteria presuppose that evaluating an argument’s strength is methodologically prior to identifying its structure. Yet, if ‘argument structure’ is a concept of analysis, then a structural analysis would precede evaluating an argument’s strength. We problematize that state-of-the-art methods to identify structures fail, because they rely on evaluative judgments, and so “put the cart before the horse.”